Phytochemical screening and in vitro antibacterial activity of Echinops kebericho Mesfin tuber extracts: experimental studies - Negasa,Jiregna Gari; Teshome,Ibsa; Sarba,Edilu Jorga; Daro,Bekiyad Shasho (PeerJ, 2024)
Background The application of plant extracts and their phytochemicals as potential treatments for bacterial illnesses has increased significantly in the last few decades. In Ethiopia, Echinops kebericho Mesfin is widely used to treat a range of illnesses in humans and animals. This study aimed to evaluate the antibacterial activity and phytochemical screening of Echinops kebericho Mesfin. Methods We carried out an in vitro experimental study after collecting the plants from their natural habitats. Then macerated in absolute methanol and petroleum ether solvents and concentrated the extracts using a rotary evaporator. In the experiment, we used Standard cultures of E. coli, K. pneumoniae, S. aureus, and P. aeruginosa. The agar-well diffusion method evaluated the antibacterial activity of the plants. The agar dilution method determined the minimum inhibitory concentration of the plant extract. Results The percentage yield of the plant extracts ranged from 6.25% to 7.85%. The methanol extract of Echinops kebericho Mesfin had the highest inhibitory effect on S. aureus (ATCC 25923) (16.67 ± 0.58 mm), followed by E. coli (ATCC 25922) (11.0 ± 1.73 mm). Phytochemical screening of leaves from the methanol and petroleum ether extracts of the plant revealed the presence of phytochemicals such as alkaloids, flavonoids, tannins, and cardiac glycosides. The present study revealed that the extracts of these plants have antibacterial activity. However, researchers should conduct further studies on the safety margin and quantitative bioactive isolation of selected medicinal plants.
Keywords: Echinops kebericho Mesfin; Phytochemical; Antibacterial activity